Memory after treatment for acute lymphoblastic leukaemia. Issue 3 (March 1992) - Rodgers, J; Britton, P G; Morris, R G; Kernahan, J; Craft, A W
Abstract : Long term survivors of acute lymphoblastic leukaemia (ALL) often experience cognitive difficulties, which may be related to impairment of memory function. Memory ability has been studied in a group of survivors of ALL along with sibling controls and in children who have received treatment for other forms of cancer. Children in the ALL group were found to have significant deficits in memory function in tasks which required the application of strategic planning behaviour. These deficits are potentially remediable by educational strategies.